Phylogenetic Tree Analysis of First Psychrobacter Sp. Strain From Blood of Iraqi Patient; A Case Report - Nuha S. Jassim1 , Sameer Abdul Ameer Alash2 , Najwa Shihab Ahmed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Psychrobacter spp. are a Gram negative bacteria, aerobic, non-motile, small, with coccobacilli shape.Originally isolated from seaweed samples and marine environments. Recently considered as rareopportunistic human pathogens. Sixty –five years old women admitted to hospital with diabetic mellitusand stage 4 pressure ulcers (PU) with seizure and mild fever 37.9 °C. A gram staining of blood culturerevealed gram negative bacteria have a cocobacilli shape. The VITEK2 system (bioMérieux) misidentify theisolate as Acinetobacter bumannii complex with low discrimination. The submission of the bacterial isolateto the GenBank BLAST search tool revealed that the Iraqi isolate show 100% homology with Psychrobactersp. From china with accession number ID: MK205167.1, the next matches with Uncultured Psychrobactersp. ( ID: KF859544.1 China) Psychrobacter pulmonis(ID: KU364058.1, India), Psychrobacter pulmonis(ID: MH550129.1, China)with 99% similarity for each one. This Psychrobacter sp. was the first isolate frombacteremia patients in Iraq. The identification based on 16S rRNA gene sequence for precisely identify thisbacteria that misidentified by VITEK2 system